Experimental and Theoretical Studies on Cu(II) Complex of N,N'-Disalicylidene-2,3-Diaminopyridine Ligand Reveal Indirect Evidence for DNA Intercalation - Koçak, A.; Yilmaz, H.; Faiz, O.; Andaç, O. (Elsevier Ltd, 2016)
A potential DNA intercalating Cu(II) complex ([CuL]) of the N,N'-disalicylidene-2,3-diaminopyridine ligand (H2L; dianion = L2-) has been synthesized and characterized. The photophysical and the DNA binding behaviors of the neutral [CuL] have been investigated both experimentally and theoretically. Experimental studies reveal that the [CuL] has a quite strong interaction with the Calf Thymus DNA (ctDNA) with Kb = (1.53 ± 0.48) × 106. Experimental bathochromism of 4 nm and hypochromism of ∼50% on the absorption band of the [CuL] at 408 nm by intercalation were reproduced by calculations. The competitive displacement experiments were carried out using Methylene Blue (MB) and Ethidium Bromide (EB). Viscosity measurements totally supported the intercalative interaction. Quantum mechanical calculations using time dependent density functional theory (TDDFT) coupled with polarizable continuum model were carried out in the proposed dimer of deoxyguanosine-monophosphate-deoxycytidine, d(GpC)2, intercalation pocket. The calculations qualitatively confirmed the intercalative binding. In addition, vertical excitation calculations showed that electronic excitations of H2L are affected by the environment and Cu2+ ion. The electronic transitions of the [CuL] are involved in mostly π-π∗ transitions but includes significant contribution from the charge transfer. According to the calculations, the electronic spectrum of the [CuL] is sensitive to the DNA intercalation because of the π-π stacking interaction between the DNA base pairs and aromatic rings of the [CuL]. © 2015 Elsevier Ltd.
Keywords: Density Functional Theory; DNA Intercalation; Salphen; Schiff Base; π-π Stacking